Corrosion Rate and Microstructural Evolution of Aluminum 2024-T3 in Nitric Acid under Various Heat Treatment Conditions - Gandhy Priyageng Bhagaskara; Wulansari, Ajeng (SAINSTECH NUSANTARA, 2025)
Aluminum alloy 2024-T3 is widely applied in aerospace structures due to its high strength-to-weight ratio, yet its corrosion behavior in aggressive acidic environments requires further optimization. This study evaluates the influence of heat treatment duration at 300 °C on the corrosion rate and microstructural evolution of Aluminum 2024-T3 immersed in 68% nitric acid (HNO₃). Specimens were prepared under four conditions: without heat treatment and with heat treatment for 1, 2, and 3 hours followed by water quenching. Corrosion testing was conducted using the ASTM G31-72 immersion method at exposure times of 168, 336, 504, and 672 hours, and corrosion rates were determined using the weight loss method, complemented by optical microstructural observation. The results indicate a progressive increase in corrosion rate with immersion time for all specimens. Untreated samples exhibited the highest corrosion rate, reaching 480.88 mpy at 672 hours, whereas heat-treated specimens demonstrated reduced corrosion rates, with the lowest value of 365.03 mpy observed in the 1-hour treatment condition, corresponding to an overall reduction of up to 11.70%. Microstructural analysis revealed a transition from dominant pitting corrosion in untreated specimens to intergranular corrosion in heat-treated samples. These findings highlight the role of thermal processing in enhancing corrosion resistance and optimizing service performance in acidic environments.